2022
DOI: 10.1007/s11764-022-01202-2
|View full text |Cite
|
Sign up to set email alerts
|

Work status changes and associated factors in a nationwide sample of Norwegian long-term breast cancer survivors

Abstract: Purpose The study aims to describe work status at diagnosis and 8 years post-diagnosis in a nationwide sample of breast cancer survivors (BCSs), and investigate associated and self-reported factors of reduced work status. Methods Women aged 20–65 years when diagnosed with stage I–III breast cancer (BC) in 2011 or 2012 were invited to participate in a questionnaire study in 2019 (n = 2803), of whom 49% (n = 1361) responded. For this sub-study, we included 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…An interruption to full-time work can be expected for patients to undergo treatment [35], with some treatment regimens requiring greater time away from work. Receipt of chemotherapy is associated with reduced likelihood of RTW [8,9,35], likely due to the negative side effects, including fatigue and decreased cognitive function (e.g., "chemo brain") [36,37]. Additionally, some treatments, such as hormone replacement therapies, can be active for long periods of time [35], extending beyond typical allotments for sick leave and prolonging side effects.…”
Section: Return To Work Challenges Amplified By Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…An interruption to full-time work can be expected for patients to undergo treatment [35], with some treatment regimens requiring greater time away from work. Receipt of chemotherapy is associated with reduced likelihood of RTW [8,9,35], likely due to the negative side effects, including fatigue and decreased cognitive function (e.g., "chemo brain") [36,37]. Additionally, some treatments, such as hormone replacement therapies, can be active for long periods of time [35], extending beyond typical allotments for sick leave and prolonging side effects.…”
Section: Return To Work Challenges Amplified By Treatmentmentioning
confidence: 99%
“…This may be amplified for those with occupations in which physical function, including arm function, is vital to job performance, and survivors may not be able to return to the same level of productivity they had before breast cancer treatment. Demographic disparities, such as income, number of dependents in the household, and living in a rural location, may also impact recovery and RTW [8][9][10]. Disparities can compound treatment outcomes, and their consideration in the treatment pathway is needed to fully understand the RTW landscape for breast cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, the challenge goes beyond return to work (RTW) and sustainable RTW (SRTW) is an issue for many BCS who often have several sick leaves or struggle to retain their jobs after RTW. [6][7][8][9][10] Employment after cancer can be affected by different factors. Evidence from studies including survivors from all cancer sites found that clinical factors, sociodemographic factors, including older age, low socio-economic status, workplace environment (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta‐analysis found that 70% of BCS return to work after the end of treatment, which was not significantly different from all cancer survivors 5 . However, the challenge goes beyond return to work (RTW) and sustainable RTW (SRTW) is an issue for many BCS who often have several sick leaves or struggle to retain their jobs after RTW 6–10 …”
Section: Introductionmentioning
confidence: 99%
“…A Norwegian study from 2017 [10] reported that up to 35% of cancer survivors experience chronic fatigue. Regardless of when they occur, late and long-term effects can significantly impair physical, psychological, or social functioning, and thus reduce cancer survivors' quality of life [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%